Assessment of correction effectivenes of psychoemitional state in pregnant women after application of assisted reproductive technologies - V.O. Beniuk; V.G. Ginzburg; L.M. Vygivska; I.V. Maidannyk; O.O. Chorna; V.F. Oleshko; Yu.L. Marushchenko; L.D. Lastovetska (Medičnì Perspektivi, 2021)
To determine the role and effectiveness of the proposed therapeutic and preventive complex in the correction of psychoemotional state in the dynamics of pregnancy in pregnant women after assisted reproductive technologies (ART) application in order to improve the tactics of antenatal observation and prevention of obstetric and perinatal complications. 299 pregnant women were comprehensively examined and a set of therapeutic and preventive measures was carried out: the main group included 249 women whose pregnancy occurred as a result of ART application. The control group consisted of 50 pregnant women with spontaneous pregnancy. The complex of measures for pregnant women after ART application included: micronized progesterone, magnesium oxide, folic acid, L-arginine aspartate, Omega-3 polyunsaturated fatty acids and long-term psychological correction – before ART program, at 8-10 weeks of pregnancy, at 16-18 weeks of pregnancy and at 28-30 weeks of pregnancy. Introduction of the proposed complex of psychoemotional correction contributed to the formation of reactive anxiety and personal anxiety levels at a moderate level in women of subgroups IA-44 (89.8%) and 43 (87.6%), IIA – 43 (89.6%) and 44 (91.7%) and IIIA – 30 (83.3%) and 26 (72.2%), which is considered to be an adaptive, physiological type during pregnancy. The positive effect of the proposed complex of psychoemotional correction demonstrates the improvement of processes of formation of type of component gestational dominant, its return to the optimal type in women of subgroup IA – 41 (83.6%), IIA – 39 (81.3%) and IIIA – 26 (72.2%) that is close to the physiological course of pregnancy and contributes to the reduction of perinatal and obstetric complications among pregnant women of these subgroups.